2012
DOI: 10.1128/aem.00046-12
|View full text |Cite
|
Sign up to set email alerts
|

The Acyl Homoserine Lactone Receptor, SdiA, of Escherichia coli and Salmonella enterica Serovar Typhimurium Does Not Respond to Indole

Abstract: In this study, we tested the hypothesis that the SdiA proteins of Escherichia coli and Salmonella enterica serovar Typhimurium respond to indole. While indole was found to have effects on gene expression and biofilm formation, these effects were not sdiA dependent. However, high concentrations of indole did inhibit N-acyl-L-homoserine lactone (AHL) sensing by SdiA. We conclude that SdiA does not respond to indole but indole can inhibit SdiA activity in E. coli and Salmonella.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
1
31
0
1
Order By: Relevance
“…We observed that the type I triazole HLs with alkyl chains extending from the triazole ring ( i.e. , I-A – I-D ) displayed trends parallel to previously reported 3-oxo acyl-HLs; 23, 30 that is, triazole HLs with short alkyl chains were LasR antagonists, while triazole HLs with longer chains were LasR agonists (see below). As the alkyl chain increased in length from propyl ( I-A , 55%) to butyl ( I-B , 75%, IC 50 value = 17.6 μM), inhibitory activity increased from moderate to strong (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…We observed that the type I triazole HLs with alkyl chains extending from the triazole ring ( i.e. , I-A – I-D ) displayed trends parallel to previously reported 3-oxo acyl-HLs; 23, 30 that is, triazole HLs with short alkyl chains were LasR antagonists, while triazole HLs with longer chains were LasR agonists (see below). As the alkyl chain increased in length from propyl ( I-A , 55%) to butyl ( I-B , 75%, IC 50 value = 17.6 μM), inhibitory activity increased from moderate to strong (Table 1).…”
Section: Resultssupporting
confidence: 86%
“…Another gene potentially regulated by SdiA is srgE, which was acquired by horizontal transfer and has an unknown function (Sabag-Daigle et al, 2012). However, according to in silico nucleotide sequence analyses performed by the same authors, the SrgE protein may be involved in type III secretion systems (Sabag-Daigle et al, 2012).…”
Section: Quorum Sensing In Salmonella Enteritidis Pt4 578mentioning
confidence: 99%
“…However, according to in silico nucleotide sequence analyses performed by the same authors, the SrgE protein may be involved in type III secretion systems (Sabag-Daigle et al, 2012).…”
Section: Quorum Sensing In Salmonella Enteritidis Pt4 578mentioning
confidence: 99%
“…However, another group determined that an indole associated decrease in biofilm formation in S. Typhimurium and E. coli was not dependent on SdiA. Instead, high indole concentrations were found to inhibit AHL detection by SdiA (Sabag-Daigle et al, 2012). …”
Section: Multidirectional Signaling In the Gut And Effect On S Typhimentioning
confidence: 99%